ARUS KOMUNIKASI INTERNAL PADA FORUM KOMUNIKASI PUTRA PUTRI PURNAWIRAWAN TNI POLRI (FKPPI) DI KABUPATEN KARIMUN - Kasirul Fadli (JURNAL MANAJEMEN PENDIDIKAN, 2019)
Internal communication flow that took place at the Retired Women's Fashion Forum TNI - POLRI (FKPPI) was not as bright as the achievements he had achieved. There are still obstacles in the process of information exchange between FKPPI chairmen and FKPPI members, one of them is lack of communication between FKPPI chairman and all members of FKPPI and vice versa among FKPPI members who are still lacking to communicate each other, giving information to each other. Commitment should be a binder in giving more impetus to the success of the organization not appropriately applied by the FKPPI board plus many inactive administrators make barriers in achieving and festive success. All and every member should be able to actively engage and cooperate in various decision-making. Through the same goals and values of organization with the purpose of members will create a commitment to achieve a better goal of the organization. This research uses qualitative approach with data collection technique through observation by doing direct observation. Population studied in this research is All Member of Communication Forum of Putri Putri Purnawirawan TNI - POLRI (FKPPI) In Karimun Regency either inactive or active still amount to 33 people according to organizational structure of management. Researchers take a predetermined sample in accordance with the technique used is Purposive sampling is to choose a sample based on the goal. Total samples taken are 10 informants who are active in the management of FKPPI. The upward pattern of communication within the Karimun District FKPPI is generally open, in which each member is given the freedom to express his opinions in the form of: ideas, suggestions, criticism or whatever else to the boss, as long as what they say can help in progress an organization. Downward communication pattern in FKPPI of Karimun Regency should run between members with its chairman. All that can happen because the communication between members is quite intimate and close to each other. Downward communication pattern in FKPPI of Karimun Regency should run between members with its chairman. All that can happen because the communication between members is quite intimate and close to each other. Good communication will certainly produce a good as well. Good relationships to build and enhance good solidarity relationships with each other. Communication barriers felt by employees in FKPPI Karimun District is sometimes the case in the management of FKPPI is a communication barrier that often happens is the lack of interest members to plan the program.